(untitled) (Journal of the College of Basic Education, 2022)
The Zn1-xCdxS alloys were prepared in evacuated quartz tubes by the method of melt quenching. The Zn1-xCdxS thin films prepared by thermal evaporation method and at different value for x, (x= 0.0, 0.1, 0.2, 0.3, 0.4 and 0.5). X-Ray diffraction technique was used to study the structure of this films and the effect of x value on it . X-ray diffraction analysis confirmed that these films are polycrystalline structure nature having f.c.c , and lattice parameters are reported.The most preferential orientation is along [111] direction for all deposited films. The lattice parameter, grain size, microstrain, dislocation density in the film are calculated and correlated with x.